2008
DOI: 10.1080/00015458.2008.11680231
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Familial Nonmedullary Thyroid Cancer in a Large Case Series

Abstract: Familial nonmedullary carcinoma of the thyroid gland occurs very rarely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…FNMTC patients with tumor recurrence-as far as stated in literature-were predominantly younger than 45 years [9,17,18]. Lupoli et al presented three of seven patients (age 22, 26, and 46 years) with vascular invasive, multifocal, and bilateral FNMTC with a tumor relapse, 3 to 6 years after surgery with one patient dying of lung metastases [18].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…FNMTC patients with tumor recurrence-as far as stated in literature-were predominantly younger than 45 years [9,17,18]. Lupoli et al presented three of seven patients (age 22, 26, and 46 years) with vascular invasive, multifocal, and bilateral FNMTC with a tumor relapse, 3 to 6 years after surgery with one patient dying of lung metastases [18].…”
Section: Discussionmentioning
confidence: 92%
“…Lupoli et al presented three of seven patients (age 22, 26, and 46 years) with vascular invasive, multifocal, and bilateral FNMTC with a tumor relapse, 3 to 6 years after surgery with one patient dying of lung metastases [18]. Zivalijevic et al reported in a series of 13 FNMTC (I:II-IV staging ratio10:3) two patients with relapse after 11 and 12 years after thyroidectomy with age at diagnosis of 33 and 42 years [9]. Grossman reported recurrence in eight of 14 patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Uglavnom se radi o naknadno utvrđenoj rodbinskoj vezi posle operativnog lečenja papilarnih tumora dijagnostikovanih citološkom analizom ili histopatološkim nalazima. U svakom slučaju, nodoznim promenama bliskih srodnika bolesnika sa malignim tumorima štitaste žlezde posvećuje se posebna pažnja (17).…”
Section: Profi Laktička Tiroidektomijaunclassified